DAMPAK KRISIS MONETER DAN KEBIJAKSANAAN PEMERINTAH TERHADAP DAYA SAING AGRIBISNIS AYAM RAS PEDAGING DI JAWA BARAT - SAPTANA -; I WAYAN RUSASTRA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2001)
Monetary and economic crisis started on the mid of 1997 has negative impact on theperformance and sustainability of poultry industry in this country. The main problem facedby broiler industry, namely: (1) Most of feed stuff are highly dependent on import; (2) Thestructure of input and output market are olygopolistic in nature; (3) Cooperative farming isnot consistently implemented; and (4) The price of input factor increased threefold due tomonetary and economic crisis. Based on those backgrounds, the objective of this study is toanalysis the impact of government policy on financial and economic feasibilities of broileragribusiness. The finding of the respective study conducted in two district (Bogor andTasikmalaya) indicated that: (1) Because of economic crisis, financial and economicprofitability of broiler industry decreases; (2) Private Cost Ratio (PCR) increased from 0,753– 0,873 to 0,851 – 0,989 due to crisis, indicating lower financial competitiveness; (3) Thevalue of DRCR before and after crisis are 0,727 – 0,976 vs. 0,790 vs. 0,917 which reveallower economic competitiveness; and (4) The value of Nominal Protection Coefficient (NPC)during the economic crisis showed that broiler industry experiencing disincentive for bothinput and output market. The implication of this study in relation with the development ofbroiler industry facing the economic globalization are as follows: (1) The vertical integrationand cooperation between smallholder broiler farming and input/output industry should bestrengthening in synergistic manner; (2) In order to generate foreign exchange and highervalue added through export and product development as well as product differentiation,vertical integration for all agribusiness subsystem in broiler industry should be implemented;and (3) The establishment of cooperative broiler farming system should be conducted in theregional news of potential market and feed stuff producing regions.